Kontekstualisasi Surat Al-Fatihah Dalam Membangun Keluarga Sakinah - Paryadi, Paryadi; Sadari, Sadari (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2024)
The sakinah family is the ideal standard of family in Islam. However, creating sakinah in the family is not an easy job. There are many variables and dynamics in family life that must be navigated. This literature study research aims to find the contextualization of the Al-Fatihah letter in building a sakinah family.  This research found the conclusion that First, a sakinah family must be built with basmallah, intention for Allah and involving Allah in every family matter. Second, the family must always be grateful for the soul mate that God has destined for them. Third, the family gives love to their partner, even though each has advantages and disadvantages. Fourth, because the afterlife is the day of retribution, you should maintain family orientation towards the afterlife so you can enter heaven with your family as a reward for protecting your family. Fifth, a sakinah family must always be in the frame of worship and rely on Allah. Sixth, when starting a family, always ask Allah for guidance and guidance to maintain the integrity of your family. Seventh, make the families of the prophets and pious people as role models, avoid following the lifestyle of the families of Christians and Jews